Ethics of Kant in Light of the Hermeneutic Reflection on Ethics - Przyłębski, Andrzej (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
Well known is the distance of Hermeneutical Philosophy – whose fundaments, based on the findings of Heidegger and Dilthey, were created by Gadamer andRicoeur – to Kant's theoretical philosophy, i.e. to his theory of knowledge. This is surprising that in the area of practical philosophy – mainly applied to ethics, to a lesser extent to policy – a reference to the ideas of the author of Critique of the Practical Reason is definitely stronger. The effect of this is that Hermeneutical Philosophy makes an important contribution to maintaining the vitality of ethical thought of Kant,to renew and nurture its spiritual heritage. This text shows, due to an analysis of the ethical considerations of Gadamer and Ricoeur, in what wayand to what extent ethical reflection in hermeneuticsderives from this heritage.